Assessment of oxygen supplementation during air travel. Issue 2 (February 1996) - Cramer, D.; Ward, S.; Geddes, D.
Abstract : BACKGROUND: The aim of this study was to simulate an in flight environment at sea level with a fractional inspired concentration of oxygen (FiO2) of 0.15 to determine how much supplemental oxygen was needed to restore a subject's oxygen saturation (SaO2) to 90% or to the level previously attained when breathing room air (FiO2 of 0.21). METHODS: Three groups were selected with normal, obstructive, and restrictive lung function. Using a sealed body plethysmograph an environment with an FiO2 of 0.15 was created and mass spectrometry was used to monitor the FiO2. Supplemental oxygen was administered to the patient by nasal cannulae. SaO2 was continuously monitored and recorded at an FiO2 of 0.21, 0.15, and 0.15 + supplemental oxygen. RESULTS: When given 2 l/m of supplemental oxygen all patients in the 15% environment returned to a similar SaO2 value as that obtained using the 21% oxygen environment. One patient with airways obstruction needed 3 l/m of supplemental oxygen to raise his SaO2 above 90%. CONCLUSIONS: This technique, which simulates an aircraft environment, enables an accurate assessment to be made of supplemental oxygen requirements.